Characteristics, outcome and predictors of one year mortality rate in patients with acute heart failure - Banović Marko; Vasiljević-Pokrajčić Zorana; Vujisić-Tešić Bosiljka; Stanković Sanja; Nedeljković Ivana; Petrović Olga; Boričić-Kostić Marija; Petrović Milan; Trifunović Danijela; Ostojić Miodrag (Vojnosanitetski Pregled)
Background/Aim. Acute heart failure (AHF) is one of the most common diseases in emergency medicine, associated with poor prognosis and high in-hospital and longterm mortality. The aim of this study was to investigate characteristics, outcomes and one year mortality of patients with AHF in the local population. Methods. This prospective study consisted of 64 consecutive unselected patients treated in the Coronary Care Unit of the Emergency Centre (Clinical Center of Serbia, Belgrade) and were followed for one year after the discharge. Results. Mean age of the patients was 63.6 ± 12.6 years and 59.4% were males. Acute congestion (43.8%) and pulmonary edema (39.1%) were the most common presentations of AHF. Mean left ventricular ejection fraction (LVEF) was 39.7% ± 9.25%, while 44.4% of the patients had LVEF ≥ 50%. At discharge, 55.9% of the patients received therapy with β-blockers, 94.9% diuretics, out of which 47.7% spironolactone, 94.9% patients were given ACE-inhibitors or angiotensin receptor blokcers (ARB). The 12-month all-cause mortality was 26.5%. Independent predictors of one year mortality were previous hospitalization due to heart disease, reduced LVEF, reduced fraction of shortening (FS) and a higher tricuspid velocity. Conclusion. One year mortality of our patients with AHF was high, similar to the known European studies. Independent predictors of one year mortality were previous hospitalization due to heart disease, reduced LVEF and LVFS and a higher tricuspid velocity.